Cytokine patterns in the pathogenesis of human leishmaniasis. - Pirmez, C (1993)
The host response to infection appears to be regulated by specific patterns of local cytokine production. In the mouse, resistance to many pathogens including Leishmania is associated with a TH1 cytokine profile, IL-2 and IFN-gamma; whereas susceptibility to infection is associated with production of TH2 cytokines, IL-4, IL-5, and IL-10. To determine the cytokine patterns of the local immune response to Leishmania infection in humans, we used the polymerase chain reaction to compare cytokine mRNAs in biopsy specimens of American cutaneous leishmaniasis. In localized cutaneous leishmaniasis and the Montenegro delayed-type hypersensitivity reaction, type 1 cytokine mRNAs such as IL-2, IFN-gamma, and lymphotoxin were relatively predominant. In the chronic and destructive mucocutaneous form of leishmaniasis, there was a mixture of type 1 and type 2 cytokines, with a striking abundance of IL-4 mRNA in lesions. These results suggest that clinical course of infection with Leishmania braziliensis in man is associated with specific local patterns of cytokine production.